2019
DOI: 10.3390/rs11111330
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 Mw 7.5 Palu Earthquake: A Supershear Rupture Event Constrained by InSAR and Broadband Regional Seismograms

Abstract: The 28 September 2018 Mw 7.5 Palu earthquake occurred at a triple junction zone where the Philippine Sea, Australian, and Sunda plates are convergent. Here, we utilized Advanced Land Observing Satellite-2 (ALOS-2) interferometry synthetic aperture radar (InSAR) data together with broadband regional seismograms to investigate the source geometry and rupture kinematics of this earthquake. Results showed that the 2018 Palu earthquake ruptured a fault plane with a relatively steep dip angle of ~85°. The preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 61 publications
6
59
0
2
Order By: Relevance
“…This value was subsequently modified to assess its effect on the calculated ΔCFS. Previous studies reported the 2018 Palu Mw 7.5 earthquake fault parameters using seismic wave, GPS, and INSAR data inversions (Bao et al, 2019;Fang et al, 2019;Socquet et al, 2019;Song et al, 2019;Ulrich et al, 2019;Wang et al, 2019aWang et al, , 2019bCevikbilen et al, 2019;USGS). The employed fault-plane segments, fault geometries, and slip distributions differed due to inversion differences in the modelling techniques and data sets.…”
Section: S2 Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…This value was subsequently modified to assess its effect on the calculated ΔCFS. Previous studies reported the 2018 Palu Mw 7.5 earthquake fault parameters using seismic wave, GPS, and INSAR data inversions (Bao et al, 2019;Fang et al, 2019;Socquet et al, 2019;Song et al, 2019;Ulrich et al, 2019;Wang et al, 2019aWang et al, , 2019bCevikbilen et al, 2019;USGS). The employed fault-plane segments, fault geometries, and slip distributions differed due to inversion differences in the modelling techniques and data sets.…”
Section: S2 Methodologymentioning
confidence: 99%
“…Previous studies have revealed the fault rupture process of the 2018 Palu Mw 7.5 earthquake using seismic wave, GPS, and InSAR data inversions (Bao et al, 2019;Fang et al, 2019;Socquet et al, 2019;Song et al, 2019;Ulrich et al, 2019;Wang et al, 2019aWang et al, , 2019bCevikbilen et al, 2019;USGS). The present study used the fault slip model developed by Song (2019) as it exhibited a geometrical simplicity and comparable slip distribution as compared to the other models (Bao et al, 2019;Socquet et al, 2019;Song et al, 2019;Wang et al, 2019).…”
Section: S1 Historical Earthquakesmentioning
confidence: 99%
See 3 more Smart Citations